2023
DOI: 10.1101/2023.02.25.530033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient cAMP production drives rapid and sustained spiking in brainstem parabrachial neurons to suppress feeding

Abstract: Brief stimuli can trigger longer lasting brain states. G protein-coupled receptors (GPCRs) could help sustain such states by coupling slow-timescale molecular signals to neuronal excitability. Brainstem parabrachial nucleus glutamatergic neurons (PBNGlut) regulate sustained brain states such as pain, and express Gs-coupled GPCRs that increase cAMP signaling. We asked whether cAMP directly influences PBNGlut excitability and behavior. Both brief tail shocks and brief optogenetic stimulation of cAMP production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These feeding-related calcium responses during biPACstimulation sessions continued to grow across trials, ultimately exceeding the amplitude of control traces (Figures 7A topmiddle and 7B). In the absence of feeding, biPAC stimulation did not excite PVH MC4R neurons in vivo 98,113 (Figures 7A and S7C-S7F). The accelerated emergence of excitation is likely caused by cAMP-mediated synaptic plasticity that strengthens excitatory inputs [114][115][116] , as whole-cell recordings in brain slices show that cAMP production by biPAC activation triggers a small but consistent potentiation of spontaneous EPSC (sEPSC) amplitudes (Figures 7C-7E; see Figures S7G-S7I for additional slice data).…”
Section: Elevating Camp In Pvh Mc4r Gradually Accelerates Satiationmentioning
confidence: 97%
See 2 more Smart Citations
“…These feeding-related calcium responses during biPACstimulation sessions continued to grow across trials, ultimately exceeding the amplitude of control traces (Figures 7A topmiddle and 7B). In the absence of feeding, biPAC stimulation did not excite PVH MC4R neurons in vivo 98,113 (Figures 7A and S7C-S7F). The accelerated emergence of excitation is likely caused by cAMP-mediated synaptic plasticity that strengthens excitatory inputs [114][115][116] , as whole-cell recordings in brain slices show that cAMP production by biPAC activation triggers a small but consistent potentiation of spontaneous EPSC (sEPSC) amplitudes (Figures 7C-7E; see Figures S7G-S7I for additional slice data).…”
Section: Elevating Camp In Pvh Mc4r Gradually Accelerates Satiationmentioning
confidence: 97%
“…Photometry measurements of Axon-GCaMP6s 97 in vivo showed that our stimulation protocol triggers short-lived calcium transients with similar amplitudes and decay kinetics in fasted and fed mice (Figures S5A-S5B), ruling out the axonexcitability hypothesis. To test the second hypothesis, we compared the clearance kinetics of cAMP produced by the bluelight-activated adenylyl cyclase, biPAC 55,98,99 . In brain slices from fasted and fed mice, cAMP clearance in PVH MC4R neurons occurred within several minutes and did not differ between fasted and fed states (Figure S5C), ruling out the cAMPclearance hypothesis.…”
Section: Competition For Camp Signaling By Opposing Hunger and Satiet...mentioning
confidence: 99%
See 1 more Smart Citation